2021
DOI: 10.1002/jmri.27566
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Artifacts Induced by B0 Inhomogeneities in Breast MRI Using Reduced‐Field‐of‐View Echo‐Planar Imaging and Enhanced Reversed Polarity Gradient Method

Abstract: Background Diffusion‐weighted (DW) echo‐planar imaging (EPI) is prone to geometric distortions due to B0 inhomogeneities. Both prospective and retrospective approaches have been developed to decrease and correct such distortions. Purpose The purpose of this work was to evaluate the performance of reduced‐field‐of‐view (FOV) acquisition and retrospective distortion correction methods in decreasing distortion artifacts for breast imaging. Coverage of the axilla in reduced‐FOV DW magnetic resonance imaging (MRI) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
(35 reference statements)
2
5
0
Order By: Relevance
“…We demonstrated consistent reductions in mean error across subjects, as well as the increases in MI between DWI b = 0 and T 2 images after correcting for distortion. This is in line with prior work that demonstrated improved similarity of DWI with T 2 anatomic imaging after RPG 17 , 18 . Inspection of data revealed some instances of increases in measured error after the application of RPG.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We demonstrated consistent reductions in mean error across subjects, as well as the increases in MI between DWI b = 0 and T 2 images after correcting for distortion. This is in line with prior work that demonstrated improved similarity of DWI with T 2 anatomic imaging after RPG 17 , 18 . Inspection of data revealed some instances of increases in measured error after the application of RPG.…”
Section: Discussionsupporting
confidence: 91%
“…Prior studies have demonstrated that B 0 inhomogeneities affect organ or lesion localization in the prostate and breast 16 , 17 , 18 . The extent of B 0 inhomogeneities and their consequent artifacts depend, in part, on the anatomic environment of a region of interest or lesion (e.g., how close the lesion is to an air-tissue interface).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated consistent reductions in mean error across subjects, as well as the increases in MI between DWI b=0 and T2 images after correcting for distortion. This is in line with prior work that demonstrated improved similarity of DWI with T2 anatomic imaging after RPG [8,10].…”
Section: Discussionsupporting
confidence: 91%
“…Prior studies have demonstrated that B0 inhomogeneities affect organ or lesion localization in the prostate and breast [7,8,10]. The extent of B0 inhomogeneities and their consequent artifacts depend, in part, on the anatomic environment of a region of interest or lesion (e.g., how close the lesion is to an air-tissue interface).…”
Section: Discussionmentioning
confidence: 99%